PENGARUH PEMBERIAN ESOP DAN KUALITAS AUDITOR TERHADAP KEINFORMATIFAN LABA DIMODERASI KEPEMILIKAN MANAJERIAL - Ayu Lestari (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2018)
The objective of the empirical study is to examine and to analyze the influence of employee stock option program (ESOP) and auditor quality on earnings informativeness proxied by earnings response coefficients on companies that adopted ESOP listed on the Indonesia Stock Exchange at year 2013-2017. This research uses moderating variables managerial ownership and uses control variables company size, default risk and industry type. Data for this research were obtained by Indonesian Capital Market Directory (ICMD), the Indonesia Stock Exchange website, the company's annual report, and stock price data from Yahoo Finance. Sample that used in this research were 18 go public companies listed on the Indonesia Stock Exchange and adopted ESOP in 2013-2017. The sampling technique used was purposive sampling method. This research uses moderation regression analysis. The results showed that employee stock option programs and auditor quality had a positive and significant influence to earnings informativeness. The test results in the moderating variable that managerial ownership cannot strengthen the relation between employee stock option program and earnings informativeness, while managerial ownership can strengthen the relation between auditor quality and earnings informativeness. Company size and default risk as control variables have a positive but not significant effect to earnings informativeness, while industry types have a positive and significant influence to earnings informativeness.